Application of Upscaling Permeability Workflow: Pore to Core Plug Scale on Malay Basin Thin Sections - Lubis, Luluan Almanna (2012)
A new approach to predict permeability at laboratory scale which can be implemented in real time on personal computer was proposed and applied on Malay Basin Thin Section. The workflow is based on combination of fluid flow simulation through 3D porous media generated from 2D image at pore scale, grain size vertical profile trends of whole image area of thin section which cover cm scale area and upscaling from pore to core plug scale (mm to cm scale). The workflow was applied on thin sections from malay basin which don’t have any bedding information. The grain size vertical profile trends which cover the whole area of thin sections were used to define the heterogeneity of full thin section images at core plug scale. The building blocks for upscaling purposes were created based on these trends. Each representative image from each blocks were selected and 2D to 3D porous media reconstruction method was applied. From this information permeability at pore scale from each blocks were estimated and then upscaling from pore to core plug scale was applied. The blind test and upscaling results on each thin section matched well with accuracy ~85 – 90 % compare to laboratory data.